2020
DOI: 10.1002/adsc.201901274
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Bioamination of Ketones in Organic Solvents at Controlled Water Activity using Immobilized ω‐Transaminases

Abstract: Compared with biocatalysis in aqueous media, the use of enzymes in neat organic solvents enables increased solubility of hydrophobic substrates and can lead to more favorable thermodynamic equilibria, avoidance of possible hydrolytic side reactions and easier product recovery. ω-Transaminases from Arthrobacter sp. (AsRÀ ωTA) and Chromobacterium violaceum (CvÀ ωTA) were immobilized on controlled porosity glass metal-ion affinity beads (EziG) and applied in neat organic solvents for the amination of 1phenoxyprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 109 publications
0
36
1
Order By: Relevance
“…66,67 The use of ow chemistry for biocatalysis continues to offer solutions to problems that have proven long-standing and hard to overcome, such as enzyme stability with immobilization, 68 improving the kinetics of an enzymatic reaction by novel reactor designs, 69 and the easier integration of organic solvents. 70 Other technological solutions, including the use of non-aqueous medias such as deep eutectic solvents (DESs), 71 or membrane separation for reaction compartmentalization, 72 provide a glimpse as to some of the potential ways biocatalysts could be applied to circumvent issues with their application.…”
Section: Future Of Biocatalysis For Fbddmentioning
confidence: 99%
“…66,67 The use of ow chemistry for biocatalysis continues to offer solutions to problems that have proven long-standing and hard to overcome, such as enzyme stability with immobilization, 68 improving the kinetics of an enzymatic reaction by novel reactor designs, 69 and the easier integration of organic solvents. 70 Other technological solutions, including the use of non-aqueous medias such as deep eutectic solvents (DESs), 71 or membrane separation for reaction compartmentalization, 72 provide a glimpse as to some of the potential ways biocatalysts could be applied to circumvent issues with their application.…”
Section: Future Of Biocatalysis For Fbddmentioning
confidence: 99%
“…Toluene was used as the reaction solvent, and the water activity (a w ) was controlled using a hydrate salt pair (i.e., Na 2 HPO 3 •5H 2 O/Na 2 HPO 4 •7H 2 O, 1:1 w w −1 ), as reported in our previous study [35]. AsR-ωTA-a recombinant (R)-selective enzyme originated from Arthrobacter sp.-was immobilized on EziG 3 (Fe Amber) controlled porosity glass beads and prepared for reactions in organic solvent, as previously reported [35,51]. The reactions were performed in dark glass vials (2 mL) with screw caps and shaken in a thermomixer at 25 • C.…”
Section: Pikat Substrate Selectionmentioning
confidence: 99%
“…As mentioned above, recurrent challenges in ωTA-catalyzed reactions using the "classical" alanine (or another α-amino acid) as the sacrificial amine donor in an aqueous environment are unfavorable reaction equilibrium and frequent enzyme inhibition by the amine product and pyruvate co-product [11,[25][26][27][28][29][30][31][32]. However, our group and others have demonstrated that these limitations can be addressed (or at least mitigated) by performing the transamination reaction in a neat organic solvent at controlled water activity (a w ) and using inexpensive 2-propylamine as the amine donor [33][34][35]. Biocatalyst recyclability and long-time stability under process conditions are also critical factors for the successful implementation of enzymes such as ω-TAs in industry, particularly in continuous flow processes [36].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations